Non Invasive Estimation of Vo2max and Physical Fitness Indices in Mazandaran University of Medical Sciences Staff - Zahra Jahanian Bahnemiri; Valiollah Dabidi Roshan; Afshin Fayaz Movaghar (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Maximum Oxygen Consumption (Vo2max) is a measurement for assessing cardiorespiratory fitness. Its direct measurement is an aggressive method that is technically and operationally difficult. This study investigated the correlation between this variable and the variables obtained from non-invasive methods of evaluation of body composition indices, step count, and physical activity. Materials and methods: This cross-sectional study was performed in 250 individuals randomly selected from the staff in Mazandaran University of Medical Sciences. Direct measurement of Vo2max was performed using the shuttle standard protocol. Physical composition indices were measured and computed using physical examination. Physical activity was measured using a short form of the International Physical Activity (IPAQ-S) and step count using step by step method. Results: Among body mass indices, only the values for neck circumference (r= 0.241) and body fat (r= 0.522) were correlated with the values of Vo2max (P= 0.000). The correlation between the values of Vo2max and the number of steps was also significant (r= 0.248, P=0.002). There was no significant correlation between IPAQ-S score and Vo2max values. Conclusion: To provide an indirect estimation model of Vo2max based on the values of body composition indices, IPAQ-S score, and step counts, it is necessary to implement similar correlational studies with high sample rates.